Inhibition of NOTCH1 signaling in tumor-initiating cells overcomes chemoresistance and promotes apoptosis - Rui, Yang; Gang, Zhan; Jun, Zhou; Weidong, Jin; Hui, Jiang (Archives of Biological Sciences, 2021)
Paper description: Aberrant upregulation of Notch1 in hepatocellular cancer (HCC) attenuates apoptosis. The role of the Notch1 signaling pathway in apoptosis inhibition in liver cancer cell lines was investigated. After silencing Notch1 expression by siRNA transfection of tumor initiating cells, the intrinsic apoptotic pathway was induced through downregulation of the PI3/AKT signaling pathway and the cells became sensitive to chemotherapeutic drug treatment. Pharmacological inactivation of Notch1 presents a potentially attractive clinical target for treating HCC. Abstract: The Notch signaling pathway is an evolutionarily conserved pathway essential for regulation of cell development and differentiation. Upregulation and activation of Notch signaling enhances the oncogenic potential of cancer cells through apoptosis resistance. The NOTCH1 expression pattern in hepatocellular cancer (HCC) and its role in apoptosis attenuation was determined. Immunohistostaining identified intensive positive staining of NOTCH1 in human HCC tissues as compared to control tissues. RT-PCR and Western blot quantification data showed that NOTCH1 and its downstream target transcription factor Hes1 were significantly upregulated in HCC cells. Based on these findings, we separated a population of CD44+ tumor-initiating cells (HepG2: >7%; SNU449: >6%) from HCC cell lines to ascertain the role of NOTCH1 in tumorigenesis. After NOTCH1-specific small interfering RNA (siRNA) transfection of tumor-initiating cells (TICs), NOTCH1 was significantly downregulated, and efficient uptake of DNA-targeting chemotherapeutic drugs was observed. Meanwhile, by flow cytometry analysis we found that the rate of apoptosis induction was significantly higher (P<0.01) and that cell viability was reduced (HepG2<23%; SNU449<28%) in siRNA transfected cells. In addition, the release of cytochrome C and activation of caspase 9 in CD44+ TICs was observed after siRNA transfection, confirming the induction of the mitochondrial-dependent intrinsic apoptotic pathway. Western blot analysis revealed inhibition of the PI3-Akt signaling pathway in siRNA-transfected TICs. These data suggest that activated NOTCH1 plays a significant role in liver cancer progression through apoptosis inhibition via regulation of PI3-Akt signaling. Therefore, pharmacological inactivation of NOTCH1 represents a clinically relevant therapeutic target for treating HCC.